A 2.6 GΩ, 1.4 μVrms current-reuse instrumentation amplifier for wearable electrocardiogram monitoring. (January 2021) - Cao, Wenfei; Liu, Yi; Liu, Shubin; Wang, Ling; Ma, Rui; Zhu, Zhangming
Abstract: This brief presents a high input impedance current-reuse instrumentation amplifier for wearable electrocardiogram monitoring. The IC has three main parts, namely, current-reuse amplifier, ripple reduction loop, and DC-servo loop. A current-reuse amplifier is introduced to realize multi-channel with one amplifier. A special chopper-stabilized technique is employed to eliminate the 1/f noise and boost the input impedance. A ripple-reduction loop is employed to suppress the ripple caused by the chopper modulator. Meanwhile, A DC-servo loop with chopper modulator is implemented to suppress the electrode offset. Fabricated in SMIC 180 nm CMOS process, the proposed instrumentation amplifier occupies an active area of 0.31 mm 2, draws 6.6 μA from a 1.8 V supply voltage, and achieves an input impedance in the order of giga-ohms, input referred noise as low as 1.4 μVrms .